Bacteriogenic Platinum Nanoparticles for Application in Nanomedicine - Bloch, Khalida; Pardesi, Karishma; Satriano, Cristina; Ghosh, Sougata (Frontiers in Chemistry, 2021)
Nanoscale materials have recently gained wide attention due to their potential to revolutionize many technology and industry sectors, including information technology, homeland security, transportation, energy, food safety, environmental science, catalysis, photonics and medicine. Among various nanoparticles, platinum nanoparticles (PtNPs) are widely used for biomedical applications, including imaging, implants, photothermal therapy and drug delivery. Indeed, PtNPs possesses intrinsic antimicrobial, antioxidant, and anticancer properties. Also, due to their remarkable catalytic activity, they are able to reduce the intracellular reactive oxygen species (ROS) levels and impair the downstream pathways leading to inflammation. Various approaches, including both physical and chemical methods, are currently employed for synthesis of PtNPs. However, the use of hazardous reaction conditions and toxic chemicals in these processes poses a potential threat to the environment and severely compromise the biocompatibility of the nanoparticles. Hereby, increasing need for exploitation of novel routes for synthesis of PtNPs has led to development of biological process of fabrication using microbes, specifically bacteria. Herein, we present a most comprehensive report on biogenic PtNPs by several bacteria like Acinetobacter calcoaceticus, Desulfovibrio alaskensis Escherichia coli, Shewanella algae, Plectonema boryanum, etc. An overview of the underlying mechanisms of both enzymatic and non-enzymatic methods of synthesis is included. Moreover, this review highlights the scope of developing optimized process to control the physicochemical properties, such as the nanoparticle surface chemistry, charge, size and shape, which, in turn, may affect their nanotoxicity and response at the biointerface for nanomedicine applications.